Estimation of Water Requirements and Value of Water in Agricultural Sector in East Java: The Case of Rice Plant - Permana, Aditya Widya; Kusumawardani, Deni (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Water resources is one of the inputs in rice production. In agricultural sector, water is considered as free good or priceless despite having a high use value. That implicated to the inefficient use of water in each provinces of Indonesia including East Java with no exception. This study aims to estimate the value of water and water requirements in agriculture especially rice in East Java. This study uses two quantitative analysis methods. The first method is the Penman-Montieth to calculate the water footprint and water requirements for rice. The second is benefit transfer method to estimate the value of water in rice production. Investigated areas are cities and municipals in East Java, while the study period is 2008 to 2011.The results showed that: (1) the average of water footprint in East Java from 2008 to 2011 was 3.556 m3/ton. This value is affected by climate change, fertilizers, and yields. (2) The average of water requirements for rice in East Java from 2008 to 2011 was 35.913.244.065 m3. This value is greater than the value of water allocation is determined by the government. (3) The estimated value of water for rice production in East Java was Rp 4.500.060 per hectare for one growing season. Keywords: Water Footprint, Water Requirements, Value of Water, AgricultureJEL: Q1, Q25